Komposisi Kimia dan Komponen Serat Berbagai Jenis Pakan Lokal yang Berasal dari Habitat Asal Kuskus dan Penangkaran - M Kayadoe; J F Koibur; H Warmetan (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2014)
The study was to examine the chemical composition and fiber components in various local feed sourced from native habitats and in cage. The research use 11 type of feed that rested on three types of feed native habitats (3 types of timber plants: Pometia pinnata, Pongamia pinnata, and Intsia bijuga and 8 types of feed from kuskus cage are three types of non wood plants: Ipomoea aquatic, Ipomoea batatas, and Brassicia spp., and five types of fruits: Carica papaya, Musa paradisiaca, Artocarpus integra, Averhoa carambala, Persea americana). Proximate and van Soest analysis was analized in the Feed and Nutrition Laboratory Fakultas Peternakan Perikanan dan Ilmu Kelautan Unipa, The laboratory of Forest Product Tecnology Fakultas Kehutanan Unipa, and BPT Ciawi, Bogor. The result showed that the type of feed sourced native habitats has a chemical compositions beter than that type of feed from captivity (cage). Besides higher fiber components contained on type of feed from his native habitat. These were consistent with research in Papua New Guinea that fibrous feed either need to overcome intestinal infleminations and possibly longer survival. The conclusions of this study were rear edin captivity possum that given the dominant feed fruits turned out to be given food from his native habitat because of higher potential for nutrient and fiber components.Key words: chemical composition, fiber components, feed, native habitats, captivity